ROLE OF INSULIN RESISTANCE IN THE PATHOGENESIS OF POLYCYSTIC OVARY SYNDROME - Celis, Alfredo (2015)
Polycystic ovary syndrome is associated with peripheral insulin, glucose intolerance and obesity hyperinsulinemia independent resistance. Moreover, there has been a remarkable correlation between the degree of hyperinsulinemia and hyperandrogenism.